The financial inclusion model based on Baitul Mal Wa Tanwil (BMT) cooperatives and community - Santoso, Bedjo; Khaliq, Ahmad (2016)
Financial inclusion (FI) is a global movement under the world bank programs and Alliance Financial Inclusion (AFI) which is sponsored by the Bill Gates Foundation. The aim of the movement is to ensure that the poor is able to access any financial services. The FI level in Indonesia achieved 32 %; it means 68% are financial transactions excluding the poor, whereas, the average figure in the world is just only 50%. The poverty rate in Indonesia is very high, it is reaching approximately 59%. Hence, FI is an urgent solution for the case of Indonesia. To tackle this issue, the Indonesian government has just started adopting FI by introducing the vision, the mission, and the concept for the efforts taken. The question is to what extent the appropriate model will be applied in Indonesia. There are two models: the AFI global model or top down model and another community model based on local values. There are pros and cons to the above issue. Some proponents have suggested the Islamic microfinance cooperative, i.e., the Baitul Mal Wa Tanwil (BMT)which is the offering of a solution based on its relationship to the poor. They do not agree with the global model. This study therefore attempts to evaluate the models and design the appropriate model for Indonesia which has special characteristics, i.e., cooperation, value driven culture, local wisdom, etc., which is neglected in most studies undertaken so far. This study is based on a qualitative approach done by conducting interviews of the stakeholders, using the deductive method to explore and design the model. This research revealed that the financial inclusion model based on Baitul Mal WaTanwil (BMT)-Cooperative is better in terms of flexibility and acceptability when compared to the global model. This is because Indonesia is the largest archipelago in the world with wide distances, diverse cultures, values, customs, and religions. To deal with the distances, wide area, and efficiency issues, the ICT mobile phone should be suitably used. The implementation of the model will strengthen the unity of Indonesia and national issues.